Isolation of Flavonoid from Jackfruit Leaves (Artocarpus heterophyllus Lamk.) and its Antioxidant Activity - Riyanti, Soraya; Sunardi, Clara; Falah, Sana Nurul (School of Pharmacy Institut Teknologi Bandung, 2013)
The flavonoid compound was successfully isolated from jackfruit leaves (Artocarpus heterophyllus Lamk.). Extraction was done by maceration with methanol-water (9:1), followed by methanol-water (1:1) as a solvent. Hydrolyzed extract was obtained by adding of 2NHCl, then extracted with ethyl acetate and monitored by thin layer chromatography (TLC) with nhexane-ethyl acetate (3:5) as a mobile phase. Separation was performed by column chromatography, followed by preparativethin layer chromatography. Purity of isolates was determined by 2-dimensional thin layer chromatography. Characterization of isolate were carried out by ultraviolet-visible spectrophotometry and infrared spectrophotometry. The result showed a maximum absorbance of bands I at 328.4 nm and 271 nm for bands II. Characterization of isolate by infrared spectrophotometry showed the presence of functional groups OH, CH, C = C, C = O, CC, and CO. Based on the data, the isolate identified as a flavonoid compound. Antioxidant activity of ethyl acetate fraction and column fraction by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) assay showed EC50 at 60.53 mg/mL and 35.27 Î¼g/mL respectively.Key words: Artocarpus heterophyllus Lamk., flavonoid, 1,1-diphenyl-2-picryl-hydrazyl (DPPH), EC50.Â AbstrakSenyawa flavonoid berhasil diisolasi dari daun belimbing (Artocarpus heterophyllus Lamk.). Ekstraksi dilakukan dengan cara maserasi menggunakan metanol-air (9:1), diikuti dengan metanol-air (1:1) sebagai pelarut. Hasi dari ekstrak yang terhidrolisis didapatkan dengan menambahkan 2NHCl, kemudian diekstraksi dengan etil asetat dan diamati menggunakan kromatografi lapis tipis (KLT) dengan campuran n-heksana-etil asetat (3:5) sebagai fase gerak. Pemisahan dilakukan menggunakan kromatografi kolom yang dilanjutkan dengan kromatografi lapis tipis preparative. Kemurnian dari isolat ditentukan dengan cara kromatografi lapis tipis 2-dimensi. Karakterisasi isolat ditunjukkan dengan spektrofotometer UV-Vis dan inframerah. Hasil spektrum menujukkan adanya absorbansi maksimum dari pita I pada 328,4 nm dan 271 nm untuk pita II. Karakterisasi dari isolat menggunakan spektrofotometer inframerah menunjukkan adanya gugus fungsional OH, CH, C=C, C=O, CC, dan CO. Berdasarkan data tersebut, isolat teridentifikasi sebagai senyawa flavonoid. Aktivitas antioksidan dari fraksi etil asetat dan fraksi kolom menggunakan pengujian 1,1-difenil-2-pikril-hidrazil (DPPH) menunjukkan EC50 pada 60,53 mg/ml dan 35,27 Î¼g/mL.Kata kunci : Artocarpus heterophyllus Lamk., flavonoid, 1,1-difenil-2-pikril-hidrazil (DPPH), EC50